(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To determine the incidence of phlebitis in patients with peripheral venous catheters and some related factors. Subjects and Methods: A prospective descriptive study with longitudinal follow-up was conducted on 60 inpatients indicated for peripheral venous catheter placement with an indwelling time >24 hours at the Internal Medicine Department 4, K Hospital, from January to March 2025. Results: The incidence of phlebitis was 18.3%. Significant related factors included age, disease severity, duration of peripheral venous catheter placement, and number of treatment courses. Conclusion: Patients with peripheral venous catheters who are older, have prolonged catheter indwelling time, and undergo multiple treatment courses are at higher risk of developing phlebitis.